1997
DOI: 10.1192/bjp.171.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Intensive in-patient and community intervention versus routine care after attempted suicide

Abstract: General implementation of an intensive in-patient and community intervention programme for suicide attempters does not seem justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 17 publications
3
97
1
1
Order By: Relevance
“…However, there were a large number of patients with multiple admissions (20%). This is consistent with the findings from other studies with readmission rates varying between 9 and 23% depending on the length of the study and location (Bialas et al, 1996;McEvedy, 1997;Van der Sande, 1997;Hawton et al, 1999). The frequency of readmission soon after the initial admission suggests that the conditions leading or predisposing to the episodes of self-harm are not resolved and that more research is required in this area.…”
Section: Discussionsupporting
confidence: 89%
“…However, there were a large number of patients with multiple admissions (20%). This is consistent with the findings from other studies with readmission rates varying between 9 and 23% depending on the length of the study and location (Bialas et al, 1996;McEvedy, 1997;Van der Sande, 1997;Hawton et al, 1999). The frequency of readmission soon after the initial admission suggests that the conditions leading or predisposing to the episodes of self-harm are not resolved and that more research is required in this area.…”
Section: Discussionsupporting
confidence: 89%
“…14,19 The only other systematic prevention studies targeting suicidal behaviors have been with college students with chronic suicidal ideation. 24 Reported treatment studies focus on adults with repeated suicide attempts 25,26 borderline personality disorder, 27,28 or both, and occasionally on youths hospitalized for suicide attempts. [29][30][31] Most interventions, whether brief or intensive, tend to be associated with positive psychosocial outcomes, such as decreased depression, 14,19,25,30,31 hopelessness, 24,25 anxiety, 19 and anger 19,28 and increased problem-solving skills.…”
mentioning
confidence: 99%
“…14,18 The observation that certain treatment plans serve to positively reinforce self-harming behaviour is well recognized, particularly in patients with borderline personality disorder. 29 Evidence is also emerging that pharmacological treatments can increase risk in certain groups at key temporal stages in treatment.…”
Section: Methodological Problems In Suicidologymentioning
confidence: 99%
“…behaviour that have produced negative findings, 11,[13][14][15][16][17][18] although clearly another explanation is that the interventions were simply ineffective. A small number of trials have shown positive findings, but such trials are often dismissed as being of limited generalizability.…”
Section: Methodological Problems In Suicidologymentioning
confidence: 99%